Odpowiedzi

2010-01-27T15:45:27+01:00
A) -4x + 3 = 11
-4x=8 / " -4
x= -2
b) 5y - 3 = -18
5y= -15 / : 5
y=-3
c) 9 - 2x = 10
2x=1
x=0,5
d) 6 + 2y = -5 + 3y
y=11
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-27T15:46:17+01:00
A) -4x + 3 = 11

-4x + 3 = 11
-4x = 11- 3
-4x = 8 /:(-4)
x = -2


b) 5y - 3 = -18

5y - 3 = -18
5y = -18 + 3
5y = -15 /:5
y = -3


c) 9 - 2x = 10

- 2x = 10 - 9
- 2x = 1 /:(-2)
x = - ½


d) 6 + 2y = -5 + 3y

6 + 2y = -5 + 3y
6 + 5 = 3y - 2y
11 = y
y = 11
1 5 1
2010-01-27T15:51:24+01:00
A) -4x=11-3
-4x=8/:(-4)
x =2
b)5y-3=-18
5y=-18+3
5y=-15/:5
y=-3
c)9-2x=10
-2x=10-9
-2x=1/:(-2)
x=0,5
d)6+2y=-5+3y
2y-3y=-5-6
-y=-11/:(-1)
y=11